Flow Analysis on Fusiform Aneurysm during Exercise Condition - Taib, I.; Osman, K.; Amirnordin, S.H.; Salleh, H. (Journal of Engineering and Technology (JET), 2012)
The dilation of fusiform aneurysm can yield unexpected predicament. The aneurysm is prone to rupture if not immediately treated. This study is focuses on investigate the flow behaviour inside the fusiform aneurysm during exercise condition under normal blood pressure (NBP) and high blood pressure (HBP). The results of this study shows the presence of the flow recirculation is observed at aneurysm region during exercise condition. The presence of the flow recirculation is proportional to the increase of flow activity at the aneurysm. The flow activity is much higher at distal end compared to proximal end region. The different of flow activity shows the different strength of the flow recirculation occurred at the aneurysm bulge. The results also show HBPE peak systole distribute the highest value of the pressure among others condition which is exhibits the high risk of the aneurysm from rupture.